International Symposium on Structural Stability in Superalloys (1968) 1968
DOI: 10.7449/1968/superalloys_1968_134_170
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformations in Nickel-Base Superalloys

Abstract: A study has been made of the phase transformations that occur during long time rupture testing of IN-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…With regard to σ precipitation, Hunt 62 showed that for RR1000 the application of a stress during thermal exposure increased the precipitation rate, and a similar effect has been observed in other polycrystalline alloys. 6365 However, Dreshfield and Ashbrook 66 and Acharya and Fuchs 67 observed the suppression of σ formation with the application of stress for a polycrystalline and a single-crystal alloy, respectively. Similarly, the rate of formation of µ, has been observed to either increase 7 or decrease 68 under an applied stress, or vary depending on the magnitude of the stress.…”
Section: Factors Affecting the Precipitation Of Tcp Phasesmentioning
confidence: 99%
“…With regard to σ precipitation, Hunt 62 showed that for RR1000 the application of a stress during thermal exposure increased the precipitation rate, and a similar effect has been observed in other polycrystalline alloys. 6365 However, Dreshfield and Ashbrook 66 and Acharya and Fuchs 67 observed the suppression of σ formation with the application of stress for a polycrystalline and a single-crystal alloy, respectively. Similarly, the rate of formation of µ, has been observed to either increase 7 or decrease 68 under an applied stress, or vary depending on the magnitude of the stress.…”
Section: Factors Affecting the Precipitation Of Tcp Phasesmentioning
confidence: 99%
“…The yield strength and the ultimate strength of the additively grown intermetallic compound at room temperature reached 100 MPa and 203 MPa, respectively. The outstanding contribution of the γ'-phase to the strengthening of the γ-γ' systems is determined by the negative temperature dependence of its yield strength and by the activation of latent plasticity, which prevents material from premature fracture [12,18,19]. R.F.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the Cr atoms allows them to occupy the sites of both components of the A 3 B compound [1,18]. But for the γ'-phase extracted from the 713C alloy, J. Mihalisin and D. Pasquine demonstrated that most of the chromium atoms are located on the aluminum sublattice; that is, they occupy the right side of the A 3 B compound [19]. Thus, chromium, when introduced into a nickel alloy, can increase the volume fraction of the γ'-phase at a given Al content [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation